2019
DOI: 10.1063/1.5111189
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deformability on the microscale flow behavior of red blood cell suspensions

Abstract: Red blood cell (RBC) deformability is important for tissue perfusion and a key determinant of blood rheology. Diseases such as diabetes, sickle cell anemia, and malaria, as well as prolonged storage, may affect the mechanical properties of RBCs altering their hemodynamic behavior and leading to microvascular complications. However, the exact role of RBC deformability on microscale blood flow is not fully understood. In the present study, we extend our previous work on healthy RBC flows in bifurcating microchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 58 publications
(106 reference statements)
1
28
2
Order By: Relevance
“…However, the magnitude of the changes in RBC deformability reported in the literature (ranging between 10% and 50% [38,65,66] to several folds [67,68]) would not support a model where such biomechanical changes alone are sufficient to cause vessel occlusion since previous studies showed that order of magnitude changes in shear modulus are required to impede RBC transit through narrow passages [46]. By contrast, our findings support a new concept where changes in the mechanical properties of the RBC membrane leading to abnormal haematocrit partitioning at bifurcations (via altered radial distributions of RBCs [69][70][71]) would reintroduce, in adult networks, the differences in WSS driving developmental vascular remodelling. Given the cross-species corroboration of important roles of WSS and RBC dynamics in vascular remodelling through different vertebrate model systems, future work should investigate the relevance of the findings to human physiology and whether the predicted WSS differences are sufficient to trigger pathological vascular remodelling.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the magnitude of the changes in RBC deformability reported in the literature (ranging between 10% and 50% [38,65,66] to several folds [67,68]) would not support a model where such biomechanical changes alone are sufficient to cause vessel occlusion since previous studies showed that order of magnitude changes in shear modulus are required to impede RBC transit through narrow passages [46]. By contrast, our findings support a new concept where changes in the mechanical properties of the RBC membrane leading to abnormal haematocrit partitioning at bifurcations (via altered radial distributions of RBCs [69][70][71]) would reintroduce, in adult networks, the differences in WSS driving developmental vascular remodelling. Given the cross-species corroboration of important roles of WSS and RBC dynamics in vascular remodelling through different vertebrate model systems, future work should investigate the relevance of the findings to human physiology and whether the predicted WSS differences are sufficient to trigger pathological vascular remodelling.…”
Section: Discussioncontrasting
confidence: 66%
“…21 The effect of deformability on the microscale flow behavior of RBC suspensions has been studied previously. 25,30,42 Hur et al 21 used an gradually expanding microfluidic chip for classification of different types of cells based on their size and deformability. They showed that flexible cells occupy equilibrium positions much closer to the channel center compared to rigid cells and used this effect to conduct label-free cancer cell enrichment.…”
Section: Trapping Of Rigid Rbcs In Downstream Vorticesmentioning
confidence: 99%
“…Recent microfluidic work reported that with an increase of stiffened RBCs present in flow, stiffened RBCs concentrate more toward the center-line of a 50μm wide channel [48], when compared to a healthy case. We do not observe a significant difference in stiff vs. healthy hematocrit profiles.…”
Section: Discussionmentioning
confidence: 99%